COVID-19 risk factors among the healthcare personnel of the Emergency Department of the Hospital María Auxiliadora, March-December 2020 - Vera Cohaila, Bernin Adderly (2021)
Objective: To determine the COVID-19 risk factors among the healthcare personnel of the Emergency Department of the Hospital María Auxiliadora from March to December 2020. Materials and methods: An observational, analytical-correlational, cross-sectional and retrospective research. The sample consisted of 117 emergency department workers. The study used surveys as technique and questionnaires as instrument for data collection. Results: Twenty-five point six four percent (25.64 %) of the study participants contracted COVID-19 through a family member, 38.46 % were doctors and 35.90 % worked as medical practitioners in another health institution. Fifty-six point four one percent (56.41 %) worked 150 or more hours per week and 74.36 % worked more than 12 hours per shift. Regarding the personal protective equipment, 78.63 % wore it correctly while 17.90 % used it incorrectly. Also, contact with a family member with COVID-19 was a risk factor for COVID-19 infection (p = 0.000, OR = 5.486). Conclusions: The results indicate that sociodemographic and occupational aspects are not risk factors for COVID-19 infection. However, having contact with an infected family member proved to be a pathological risk factor